2023
DOI: 10.3390/neurolint15010026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Human Microbiota in Myasthenia Gravis: A Narrative Review

Abstract: Myasthenia gravis (MG) is an autoimmune neuromuscular disease characterized by fluctuating weakness of the skeletal muscles. Although antibodies against the neuromuscular junction components are recognized, the MG pathogenesis remains unclear, even if with a well-known multifactorial character. However, the perturbations of human microbiota have been recently suggested to contribute to MG pathogenesis and clinical course. Accordingly, some products derived from commensal flora have been demonstrated to have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…However, the related molecular and cellular mechanisms are not clear. Some studies also evidence that behavioral phenotypes can be transmitted from humans to animals via transplantation/translocation of the gut microbiota [7]. This emphasizes the role of MBG alterations in ND.…”
Section: Changes In the Mgb Axis And Neuroinflammationmentioning
confidence: 96%
See 2 more Smart Citations
“…However, the related molecular and cellular mechanisms are not clear. Some studies also evidence that behavioral phenotypes can be transmitted from humans to animals via transplantation/translocation of the gut microbiota [7]. This emphasizes the role of MBG alterations in ND.…”
Section: Changes In the Mgb Axis And Neuroinflammationmentioning
confidence: 96%
“…MG cases compared with age-matched controls show a characteristic composition of the oral and gut microbiota, with a typical increase in Streptococcus and Bacteroides and a reduction in Clostridia, as well as a reduction in short-chain fatty acids. Moreover, it has been demonstrated that restoration of gut microbiota disorder after probiotic administration determines an improvement in symptoms in MG cases [7].…”
Section: Changes In the Mgb Axis And Neuroinflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, recent evidence has demonstrated that another crucial determinant (trigger) of the development of several diseases is microbial dysfunction or, more accurately, dysbiosis. Dysbiosis has been shown to impact the development and progression of numerous human diseases, ranging from immune diseases, cardiovascular diseases, neurodegenerative diseases, and cancer [18][19][20][21][22]. The very relevant role of microbiota and microbiome (its genome) has led to their being considered as the second system of control of the functions of all the organs and tissues of the human body after the brain.…”
Section: Microbiome and Allmentioning
confidence: 99%
“…In recent years, growing literature has centered its interest on the role of the mechanisms related to aging and sex-related factors and able in modulating and impairing immune system [1][2][3][4][5][6][7][8]. This last is composed, as well recognized, by two components, the innate and clonotypic compartments, which protect the organisms by external and internal pathogens and interact with other compartments of the same organism, such as the microbiota and central nervous system (CNS) [4][5][6][7][8]. Aging, as physiological condition, impairs cognitive and physical functions, such as the activities of immune system.…”
Section: Introductionmentioning
confidence: 99%